Correlation Between Plasma CircRNA-089763 and Postoperative Cognitive Dysfunction in Elderly Patients Undergoing Non-cardiac Surgery - Zhou, Hongli; Li, Fuyu; Ye, Wanlin; Wang, Maozhou; Zhou, Xian; Feng, Jianguo; Liu, Li; Wang, Xiaobin (Frontiers in Behavioral Neuroscience, 2020)
In our previous experiment, we found that circRNA-089763 had abnormal levels in the plasma exosomes of patients with postoperative cognitive dysfunction (POCD) after cardiac surgery. Therefore, the aim of this study was to further investigate the relationship between plasma circRNA-089763 level and POCD in elderly patients after non-cardiac surgery. A prospective cohort study was conducted to select elderly patients undergoing elective non-cardiac surgery. A total of 72 patients were enrolled in this study, and cognitive functions were assessed one day before and three days after surgery by a series of neuropsychological measurements. Next, patients were divided into POCD and non-POCD (NPOCD) groups according to the Z score method. Blood was collected the day before and three days day after surgery, and the plasma circRNA-089763 level was detected by quantitative real-time polymerase chain reaction (qRT-PCR). Then, the difference and correlation in plasma circRNA-089763 level between the POCD and NPOCD groups were analyzed. On the third day after surgery, the incidence of POCD was 30.56%. Compared with the NPOCD group, the relative level of circRNA-089763 in the POCD group was 2.41 times higher than that in the NPOCD group (t = 4.711, p < 0.001), patients in POCD group had higher age (t = 5.971, p < 0.001), higher ASA classification (χ2 = 14.726, p < 0.001), less years of education (t = 2.449, p = 0.017), more intraoperative blood loss (t = 3.196, p = 0.002) and higher visual analogue scale(VAS) scores (t = 10.45, p < 0.001). The binary logistic regression analysis showed that the circRNA-089763 level, age and intraoperative blood loss were independently associated with POCD (OR: 2.75, 95%CI: 1.261–5.999, p = 0.011; OR: 1.32, 95%CI: 1.114–1.565, p = 0.001; OR: 1.017, 95%CI: 1.004–1.03, p = 0.011). These results demonstrated that the circRNA-089763 plasma level was related to POCD after non-cardiac surgery in elderly patients.